2020
DOI: 10.3390/cells9040973
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults with Physical Frailty and Sarcopenia Show Increased Levels of Circulating Small Extracellular Vesicles with a Specific Mitochondrial Signature

Abstract: Mitochondrial dysfunction and systemic inflammation are major factors in the development of sarcopenia, but the molecular determinants linking the two mechanisms are only partially understood. The study of extracellular vesicle (EV) trafficking may provide insights into this relationship. Circulating small EVs (sEVs) from serum of 11 older adults with physical frailty and sarcopenia (PF&S) and 10 controls were purified and characterized. Protein levels of three tetraspanins (CD9, CD63, and CD81) and selected m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 55 publications
4
53
0
2
Order By: Relevance
“…Recent findings by our group support the hypothesis of mitochondrial impairment among the underlying pathogenetic mechanisms of sarcopenia [18]. In particular, as a result of failing quality control systems [91,[95][96][97], the release of oxidized cell-free mtDNA and other mitochondrial components within MDVs have been associated with systemic inflammation in older adults with PF&S [7].…”
Section: Inflammation-related Biomarkerssupporting
confidence: 73%
See 3 more Smart Citations
“…Recent findings by our group support the hypothesis of mitochondrial impairment among the underlying pathogenetic mechanisms of sarcopenia [18]. In particular, as a result of failing quality control systems [91,[95][96][97], the release of oxidized cell-free mtDNA and other mitochondrial components within MDVs have been associated with systemic inflammation in older adults with PF&S [7].…”
Section: Inflammation-related Biomarkerssupporting
confidence: 73%
“…The decline in physical function is, indeed, the most evident change that occurs during sarcopenia, and a cardinal criterion for the identification of PF&S [7][8][9][10]. Physical function refers to a construct encompassing simple single-joint (e.g., handgrip strength) and multi-joint complex movements (e.g., walking speed), and may be assessed through a large array of tests [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These vesicles transfer information between cells through several categories of cargo-enriched biomolecules (i.e., proteins, lipids, nucleic acids, and sugars), each of them selectively influencing different cellular domains. Picca et al, demonstrated that older adults with physical frailty and sarcopenia show increased levels of circulating small extracellular vesicles with a specific mitochondrial signature [12].…”
mentioning
confidence: 99%